Preparation process of zirconium oxide composite antibacterial repair material

By adding KCl, urea and PVA to zirconia ceramics, and preparing zirconia composite antibacterial repair materials by ultrasonic cleaning and freeze-drying, the problems of degradation of brittleness and mechanical properties of zirconia ceramics are solved, and higher density is achieved and fracture resistance.

CN119430275APending Publication Date: 2025-02-14HUNAN VSMILE BIOTECHNOLOGY CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411323524.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The application of zirconia ceramics in the dentistry field is limited by the problems of its brittleness and mechanical properties in the oral environment, which affects its service performance and reliability.

Method used

The preparation process of zirconia composite antibacterial repair materials is adopted. By adding KCl, urea and PVA, and ultrasonic cleaning and freeze-drying, the three-dimensional network structure of the combustion reaction is broken, the reaction is weakened, and the small particle size powder is obtained. And form a thin film through PVA adsorption, reduce friction and improve molding density.

Benefits of technology

It effectively inhibits the generation of hard agglomeration of particles, reduces agglomeration between powder particles, improves the density and fracture resistance of the repair material, and enhances its mechanical properties in the oral environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005054712360000081
    Figure BDA0005054712360000081
  • Figure BDA0005054712360000131
    Figure BDA0005054712360000131
Patent Text Reader

Abstract

The invention discloses a preparation process of a zirconium oxide composite antibacterial repair material, which comprises the following steps: step 1, weighing ZrO (NO3) 2.2 H2O to prepare a solution, and heating and stirring the solution in a heating stirrer; 2, sequentially adding 6% mol of Y (NO3) 3.6 H2O and KCl into the liquid in the step 1, and continuously heating and stirring until the Y (NO3) 3.6 H2O and the KCl are dissolved; step 3, adding CH4N2O into the solution obtained in the step 2, and heating and stirring until CH4N2O is dissolved; 4, when the nitrate mixed solution is concentrated into viscous liquid, heating is stopped, the viscous liquid is poured into a crucible, the crucible is placed in a resistance furnace, ignition is conducted at the constant temperature, and after heat preservation is conducted for two minutes, powder is obtained; the PVA is adsorbed on the surfaces of the powder particles, so that a layer of film is formed among the powder particles for reducing friction force, the powder has high apparent density after granulation and low volume compression ratio during forming, the powder is easily pressed into a repair material with a compact structure, pores on the surface and in the repair material are reduced, and the repair material is not easy to break.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of repair materials, and in particular to a preparation process of a zirconium oxide composite antibacterial repair material. Background Art

[0002] Zirconia has three crystal forms: monoclinic (m-phase), tetragonal (t-phase), and cubic (c-phase), all of which undergo crystal transformations at different temperatures. If t-phase zirconia can be stable at room temperature, the tm martensitic transformation can be exploited to improve its toughness. This can typically be achieved by adding rare earth stabilizers such as Y2O3, CeO2, and YbO to stabilize t-phase zirconia at room temperature. As a ceramic used in biomaterials, zirconia not only possesses high strength and toughness but also exhibits excellent compatibility and affinity with biological tissues. Currently, there is an increasing demand for functionalized dental ceramics that are beneficial to human health. With the improvement of the comprehensive mechanical properties of dental zirconia ceramics and the future demand for health-enhancing functionalization, zirconia ceramics will be more widely used in the dental field. However, the inherent brittleness of dental zirconia and the decline in mechanical properties in the oral environment can affect its service performance and reliability. Summary of the Invention

[0003] In view of the shortcomings of the prior art, the present invention solves the technical problems by adopting the following technical solution: the preparation process of the zirconium oxide composite antibacterial repair material of the present invention comprises the following steps:

[0004] Step 1: Weigh ZrO(NO3)2.2H2O to make a solution, place it in a heating stirrer and heat and stir;

[0005] Step 2: Add 6% mol Y(NO3)3.6H2O and KCl to the liquid in step 1, continue heating and stirring until dissolved;

[0006] Step 3: Add CH4N2O to step 2, heat and stir until dissolved;

[0007] Step 4: When the nitrate mixed solution is concentrated into a viscous liquid, stop heating, pour the viscous liquid into a crucible, place it in a resistance furnace, ignite it at a constant temperature, and keep it warm for two minutes to obtain a powder;

[0008] Step 5: Pour the powder into a beaker, add distilled water and stir to dissolve, use a sedimentation machine to filter and remove chloride ions, filter and wash five times, and finally add silver nitrate solution to the filtrate for testing. If no precipitate is produced, there is no chloride ion;

[0009] Step 6: Replace the distilled water with anhydrous ethanol and clean with an ultrasonic cleaner for ten minutes;

[0010] Step 7: Place the wet powder into a freeze dryer to dry it to obtain powder;

[0011] Step 8: Weigh the flocculent PVA solid and stir it in a water bath at high temperature to prepare a 5% PVA solution. Weigh 10g of the powder, add it to the PVA solution, and grind it evenly in a mortar.

[0012] Step 9: The granulated powder is sieved through 50-mesh, 120-mesh and 300-mesh sieves respectively. The particles that can pass through the 300-mesh sieve are fine particles, those between 120-300 mesh are medium particles, and those between 50-120 mesh are coarse particles.

[0013] Step 10: According to the set particle size distribution, weigh 6g of coarse, medium and fine powders and put them into the mold;

[0014] Step 11: Slowly pressurize the sample with a pressure testing machine and then maintain the pressure. The repair material after dry pressing is subjected to 200 MPa cold isostatic pressing and the repair material is obtained after maintaining the pressure.

[0015] Preferably, the concentration of the solution in step 1 is 0.085 mol / L to 0.34 mol / L.

[0016] Preferably, in step 3, the ratio of urea to metal nitrate is 0.5-1.5.

[0017] Preferably, in step 4, the temperature of the constant temperature ignition is 400°C-600°C.

[0018] Preferably, in step 3, when the ratio of urea to metal nitrate is 1.5, concentrated nitric acid needs to be added.

[0019] Preferably, the ratio of KCl to metal nitrate is 3-5.

[0020] Preferably, the mass percentage of the flocculent PVA solid is 4 wt%-24 wt%.

[0021] Preferably, the ratio of coarse, medium and fine powders in step 10 is 6:3:1 or 5:4:1 or 0:7:3.

[0022] Preferably, in step 11, the pressurization pressure of the testing machine is 80Mpa-160Mpa, and the pressure holding time is 20 minutes.

[0023] The beneficial effects of the present invention are as follows:

[0024] 1. The present invention breaks the three-dimensional network structure of the powder synthesized by the combustion reaction by adding KCl, which reduces the intensity of the reaction and leads to impure products. At the same time, a large amount of gas is released during the reaction, forming an airflow to impact the product, and it is easy to obtain a powder with a small particle size. The dry powder is obtained by ultrasonic washing combined with freeze drying, avoiding the pore collapse phenomenon caused by the surface tension of the solid-liquid interface during the drying process, thereby effectively suppressing the generation of hard agglomeration of particles. The shock waves and microjets generated by the ultrasonic cavitation have a pulverizing effect, which is used to disperse the particles and reduce the agglomeration between the powder particles.

[0025] 2. The present invention uses PVA to be adsorbed on the surface of powder particles, so that a thin film is formed between the powder particles to reduce friction. After granulation, the loose density of the powder is large, the volume compression rate during molding is small, and it is easy to be pressed into a repair material with a dense structure. The pores on the surface and inside of the repair material are reduced, and it is not easy to break. DETAILED DESCRIPTION

[0026] The present invention will be described in further detail below with reference to specific embodiments. The embodiments of the present invention are provided for purposes of illustration and description and are not intended to be exhaustive or to limit the invention to the disclosed forms. Many modifications and variations will be apparent to those skilled in the art. The embodiments are chosen and described to better illustrate the principles and practical applications of the present invention and to enable those skilled in the art to understand the present invention and design various embodiments with various modifications suitable for specific applications.

[0027] Preparation Example 1

[0028] Step 1: Weigh ZrO(NO3)2.2H2O to prepare a solution with a concentration of 0.085 mol / L, and place it in a heating stirrer while heating and stirring;

[0029] Step 2: Add 6% mol Y(NO3)3.6H2O and KCl to the liquid in step 1 in sequence, with the ratio of KCl to metal nitrate being 3, and continue heating and stirring until dissolved;

[0030] Step 3: Add CH4N2O to step 2, with the ratio of urea to metal nitrate being 0.5, and heat and stir until dissolved;

[0031] Step 4: When the nitrate mixed solution is concentrated into a viscous liquid, stop heating, pour the viscous liquid into a crucible, place it in a resistance furnace, and ignite it at a constant temperature of 400°C. After keeping the temperature for two minutes, a powder is obtained;

[0032] Step 5: Pour the powder into a beaker, add distilled water and stir to dissolve, use a sedimentation machine to filter and remove chloride ions, filter and wash five times, and finally add silver nitrate solution to the filtrate for testing. If no precipitate is produced, there is no chloride ion;

[0033] Step 6: Replace the distilled water with anhydrous ethanol and clean with an ultrasonic cleaner for ten minutes;

[0034] Step 7: Place the wet powder into a freeze dryer for drying to obtain powder.

[0035] Preparation Example 2

[0036] Step 1: Weigh ZrO(NO3)2.2H2O to prepare a solution with a concentration of 0.85 mol / L, and place it in a heating stirrer while heating and stirring;

[0037] Step 2: Add 6% mol Y(NO3)3.6H2O and KCl to the liquid in step 1 in sequence, with the ratio of KCl to metal nitrate being 4, and continue heating and stirring until dissolved;

[0038] Step 3: Add CH4N2O to step 2, with the ratio of urea to metal nitrate being 1, and heat and stir until dissolved;

[0039] Step 4: When the nitrate mixed solution is concentrated into a viscous liquid, stop heating, pour the viscous liquid into a crucible, place it in a resistance furnace, and ignite it at a constant temperature of 500°C. After keeping the temperature for two minutes, a powder is obtained;

[0040] Step 5: Pour the powder into a beaker, add distilled water and stir to dissolve, use a sedimentation machine to filter and remove chloride ions, filter and wash five times, and finally add silver nitrate solution to the filtrate for testing. If no precipitate is produced, there is no chloride ion;

[0041] Step 6: Replace the distilled water with anhydrous ethanol and clean with an ultrasonic cleaner for ten minutes;

[0042] Step 7: Place the wet powder into a freeze dryer for drying to obtain powder.

[0043] Preparation Example 3

[0044] Step 1: Weigh ZrO(NO3)2.2H2O to prepare a solution with a concentration of 0.85 mol / L, and place it in a heating stirrer while heating and stirring;

[0045] Step 2: Add 6% mol Y(NO3)3.6H2O and KCl to the liquid in step 1 in sequence, with the ratio of KCl to metal nitrate being 5, and continue heating and stirring until dissolved;

[0046] Step 3: Add CH4N2O to step 2, with the ratio of urea to metal nitrate being 1.5, add concentrated nitric acid, and heat and stir until dissolved;

[0047] Step 4: When the nitrate mixed solution is concentrated into a viscous liquid, stop heating, pour the viscous liquid into a crucible, place it in a resistance furnace, and ignite it at a constant temperature of 600°C. After keeping the temperature for two minutes, a powder is obtained;

[0048] Step 5: Pour the powder into a beaker, add distilled water and stir to dissolve, use a sedimentation machine to filter and remove chloride ions, filter and wash five times, and finally add silver nitrate solution to the filtrate for testing. If no precipitate is produced, there is no chloride ion;

[0049] Step 6: Replace the distilled water with anhydrous ethanol and clean with an ultrasonic cleaner for ten minutes;

[0050] Step 7: Place the wet powder into a freeze dryer for drying to obtain powder.

[0051] Preparation Example 4

[0052] Step 1: Weigh ZrO(NO3)2.2H2O to prepare a solution with a concentration of 0.17 mol / L, and place it in a heating stirrer while heating and stirring;

[0053] Step 2: Add 6% mol Y(NO3)3.6H2O and KCl to the liquid in step 1 in sequence, with the ratio of KCl to metal nitrate being 5, and continue heating and stirring until dissolved;

[0054] Step 3: Add CH4N2O to step 2, with the ratio of urea to metal nitrate being 0.5, and heat and stir until dissolved;

[0055] Step 4: When the nitrate mixed solution is concentrated into a viscous liquid, stop heating, pour the viscous liquid into a crucible, place it in a resistance furnace, and ignite it at a constant temperature of 500°C. After keeping the temperature for two minutes, a powder is obtained;

[0056] Step 5: Pour the powder into a beaker, add distilled water and stir to dissolve, use a sedimentation machine to filter and remove chloride ions, filter and wash five times, and finally add silver nitrate solution to the filtrate for testing. If no precipitate is produced, there is no chloride ion;

[0057] Step 6: Replace the distilled water with anhydrous ethanol and clean with an ultrasonic cleaner for ten minutes;

[0058] Step 7: Place the wet powder into a freeze dryer for drying to obtain powder.

[0059] Preparation Example 5

[0060] Step 1: Weigh ZrO(NO3)2.2H2O to prepare a solution with a concentration of 0.17 mol / L, and place it in a heating stirrer while heating and stirring;

[0061] Step 2: Add 6% mol Y(NO3)3.6H2O and KCl to the liquid in step 1 in sequence, with the ratio of KCl to metal nitrate being 3, and continue heating and stirring until dissolved;

[0062] Step 3: Add CH4N2O to step 2, with the ratio of urea to metal nitrate being 1, and heat and stir until dissolved;

[0063] Step 4: When the nitrate mixed solution is concentrated into a viscous liquid, stop heating, pour the viscous liquid into a crucible, place it in a resistance furnace, and ignite it at a constant temperature of 600°C. After keeping the temperature for two minutes, a powder is obtained;

[0064] Step 5: Pour the powder into a beaker, add distilled water and stir to dissolve, use a sedimentation machine to filter and remove chloride ions, filter and wash five times, and finally add silver nitrate solution to the filtrate for testing. If no precipitate is produced, there is no chloride ion;

[0065] Step 6: Replace the distilled water with anhydrous ethanol and clean with an ultrasonic cleaner for ten minutes;

[0066] Step 7: Place the wet powder into a freeze dryer for drying to obtain powder.

[0067] Preparation Example 6

[0068] Step 1: Weigh ZrO(NO3)2.2H2O to prepare a solution with a concentration of 0.17 mol / L, and place it in a heating stirrer while heating and stirring;

[0069] Step 2: Add 6% mol Y(NO3)3.6H2O and KCl to the liquid in step 1 in sequence, with the ratio of KCl to metal nitrate being 4, and continue heating and stirring until dissolved;

[0070] Step 3: Add CH4N2O to step 2, with the ratio of urea to metal nitrate being 1.5, add concentrated nitric acid, and heat and stir until dissolved;

[0071] Step 4: When the nitrate mixed solution is concentrated into a viscous liquid, stop heating, pour the viscous liquid into a crucible, place it in a resistance furnace, and ignite it at a constant temperature of 400°C. After keeping the temperature for two minutes, a powder is obtained;

[0072] Step 5: Pour the powder into a beaker, add distilled water and stir to dissolve, use a sedimentation machine to filter and remove chloride ions, filter and wash five times, and finally add silver nitrate solution to the filtrate for testing. If no precipitate is produced, there is no chloride ion;

[0073] Step 6: Replace the distilled water with anhydrous ethanol and clean with an ultrasonic cleaner for ten minutes;

[0074] Step 7: Place the wet powder into a freeze dryer for drying to obtain powder.

[0075] Preparation Example 7

[0076] Step 1: Weigh ZrO(NO3)2.2H2O to prepare a solution with a concentration of 0.34 mol / L, and place it in a heating stirrer while heating and stirring;

[0077] Step 2: Add 6% mol Y(NO3)3.6H2O and KCl to the liquid in step 1 in sequence, with the ratio of KCl to metal nitrate being 4, and continue heating and stirring until dissolved;

[0078] Step 3: Add CH4N2O to step 2, with the ratio of urea to metal nitrate being 0.5, and heat and stir until dissolved;

[0079] Step 4: When the nitrate mixed solution is concentrated into a viscous liquid, stop heating, pour the viscous liquid into a crucible, place it in a resistance furnace, and ignite it at a constant temperature of 600°C. After keeping the temperature for two minutes, a powder is obtained;

[0080] Step 5: Pour the powder into a beaker, add distilled water and stir to dissolve, use a sedimentation machine to filter and remove chloride ions, filter and wash five times, and finally add silver nitrate solution to the filtrate for testing. If no precipitate is produced, there is no chloride ion;

[0081] Step 6: Replace the distilled water with anhydrous ethanol and clean with an ultrasonic cleaner for ten minutes;

[0082] Step 7: Place the wet powder into a freeze dryer for drying to obtain powder.

[0083] Preparation Example 8

[0084] Step 1: Weigh ZrO(NO3)2.2H2O to prepare a solution with a concentration of 0.34 mol / L, and place it in a heating stirrer while heating and stirring;

[0085] Step 2: Add 6% mol Y(NO3)3.6H2O and KCl to the liquid in step 1 in sequence, with the ratio of KCl to metal nitrate being 5, and continue heating and stirring until dissolved;

[0086] Step 3: Add CH4N2O to step 2, with the ratio of urea to metal nitrate being 1, and heat and stir until dissolved;

[0087] Step 4: When the nitrate mixed solution is concentrated into a viscous liquid, stop heating, pour the viscous liquid into a crucible, place it in a resistance furnace, and ignite it at a constant temperature of 400°C. After keeping the temperature for two minutes, a powder is obtained;

[0088] Step 5: Pour the powder into a beaker, add distilled water and stir to dissolve, use a sedimentation machine to filter and remove chloride ions, filter and wash five times, and finally add silver nitrate solution to the filtrate for testing. If no precipitate is produced, there is no chloride ion;

[0089] Step 6: Replace the distilled water with anhydrous ethanol and clean with an ultrasonic cleaner for ten minutes;

[0090] Step 7: Place the wet powder into a freeze dryer for drying to obtain powder.

[0091] Preparation Example 9

[0092] Step 1: Weigh ZrO(NO3)2.2H2O to prepare a solution with a concentration of 0.34 mol / L, and place it in a heating stirrer while heating and stirring;

[0093] Step 2: Add 6% mol Y(NO3)3.6H2O and KCl to the liquid in step 1 in sequence, with the ratio of KCl to metal nitrate being 3, and continue heating and stirring until dissolved;

[0094] Step 3: Add CH4N2O to step 2, with the ratio of urea to metal nitrate being 1.5, add concentrated nitric acid, and heat and stir until dissolved;

[0095] Step 4: When the nitrate mixed solution is concentrated into a viscous liquid, stop heating, pour the viscous liquid into a crucible, place it in a resistance furnace, and ignite it at a constant temperature of 500°C. After keeping the temperature for two minutes, a powder is obtained;

[0096] Step 5: Pour the powder into a beaker, add distilled water and stir to dissolve, use a sedimentation machine to filter and remove chloride ions, filter and wash five times, and finally add silver nitrate solution to the filtrate for testing. If no precipitate is produced, there is no chloride ion;

[0097] Step 6: Replace the distilled water with anhydrous ethanol and clean with an ultrasonic cleaner for ten minutes;

[0098] Step 7: Place the wet powder into a freeze dryer for drying to obtain powder.

[0099] Particle size test results:

[0100]

[0101] The results of particle size detection show that the addition of KCl breaks the three-dimensional network structure of the powder synthesized by the combustion reaction, the intensity of the reaction is weakened, and the product is impure. At the same time, a large amount of gas is released during the reaction, forming an airflow to impact the product, which makes it easy to obtain powder with small particle size. The dry powder is obtained by ultrasonic washing combined with freeze drying, which avoids the pore collapse phenomenon caused by the surface tension of the solid-liquid interface during the drying process, thereby effectively inhibiting the formation of hard agglomeration of particles. The shock waves and microjets generated by ultrasonic cavitation have a pulverizing effect, which is used to disperse the particles and reduce the agglomeration between powder particles.

[0102] Example 1

[0103] Weigh 24 wt% flocculent PVA solid and stir in a water bath at high temperature to prepare a 5% PVA solution. Weigh 10 g of the powder from Preparation Example 1, add it to the PVA solution, and grind it evenly in a mortar.

[0104] The powder after granulation is sieved through 50 mesh, 120 mesh and 300 mesh sieves respectively. The particles that can pass through 300 mesh sieve are fine particles, those between 120-300 mesh are medium particles, and those between 50-120 mesh are coarse particles.

[0105] According to the set particle size distribution, weigh 6g of coarse, medium and fine powders in total, with the coarse, medium and fine powders ratio of 0:7:3, and put them into the mold;

[0106] The sample was slowly pressurized by a pressure testing machine and then maintained under pressure. The pressurization pressure of the testing machine was 80 MPa, and the holding time was 20 minutes. The repair material after dry pressing was subjected to 200 MPa cold isostatic pressing, and the repair material was obtained after maintaining the pressure.

[0107] Example 2

[0108] Weigh 4 wt% flocculent PVA solid and stir in a water bath at high temperature to prepare a 5% PVA solution. Weigh 10 g of the powder from Preparation Example 1, add it to the PVA solution, and grind it evenly in a mortar.

[0109] The powder after granulation is sieved through 50 mesh, 120 mesh and 300 mesh sieves respectively. The particles that can pass through 300 mesh sieve are fine particles, those between 120-300 mesh are medium particles, and those between 50-120 mesh are coarse particles.

[0110] According to the set particle size distribution, weigh 6g of coarse, medium and fine powders in total, with the coarse, medium and fine powders in a ratio of 5:4:1, and put them into the mold;

[0111] The sample was slowly pressurized by a pressure testing machine and then maintained under pressure. The pressurization pressure of the testing machine was 160 MPa, and the holding time was 20 minutes. The repair material after dry pressing was subjected to 200 MPa cold isostatic pressing, and the repair material was obtained after maintaining the pressure.

[0112] Example 3

[0113] Weigh 24 wt% flocculent PVA solid and stir in a water bath at high temperature to prepare a 5% PVA solution. Weigh 10 g of the powder from Preparation Example 1, add it to the PVA solution, and grind it evenly in a mortar.

[0114] The powder after granulation is sieved through 50 mesh, 120 mesh and 300 mesh sieves respectively. The particles that can pass through 300 mesh sieve are fine particles, those between 120-300 mesh are medium particles, and those between 50-120 mesh are coarse particles.

[0115] According to the set particle size distribution, weigh 6g of coarse, medium and fine powders in total, with the coarse, medium and fine powders in a ratio of 6:3:1, and put them into the mold;

[0116] The sample was slowly pressurized by a pressure testing machine and then maintained under pressure. The pressurization pressure of the testing machine was 160 MPa, and the holding time was 20 minutes. The repair material after dry pressing was subjected to 200 MPa cold isostatic pressing, and the repair material was obtained after maintaining the pressure.

[0117] Example 4

[0118] Weigh 4 wt% flocculent PVA solid and stir in a water bath at high temperature to prepare a 5% PVA solution. Weigh 10 g of the powder from Preparation Example 1, add it to the PVA solution, and grind it evenly in a mortar.

[0119] The powder after granulation is sieved through 50 mesh, 120 mesh and 300 mesh sieves respectively. The particles that can pass through 300 mesh sieve are fine particles, those between 120-300 mesh are medium particles, and those between 50-120 mesh are coarse particles.

[0120] According to the set particle size distribution, weigh 6g of coarse, medium and fine powders in total, with the coarse, medium and fine powders ratio of 0:7:3, and put them into the mold;

[0121] The sample was slowly pressurized by a pressure testing machine and then maintained under pressure. The pressurization pressure of the testing machine was 120 MPa, and the holding time was 20 minutes. The repair material after dry pressing was subjected to 200 MPa cold isostatic pressing, and the repair material was obtained after maintaining the pressure.

[0122] Example 5

[0123] Weigh 14 wt% flocculent PVA solid and stir in a water bath at high temperature to prepare a 5% PVA solution. Weigh 10 g of the powder from Preparation Example 1, add it to the PVA solution, and grind it evenly in a mortar.

[0124] The powder after granulation is sieved through 50 mesh, 120 mesh and 300 mesh sieves respectively. The particles that can pass through 300 mesh sieve are fine particles, those between 120-300 mesh are medium particles, and those between 50-120 mesh are coarse particles.

[0125] According to the set particle size distribution, weigh 6g of coarse, medium and fine powders in total, with the coarse, medium and fine powders ratio of 0:7:3, and put them into the mold;

[0126] The sample was slowly pressurized by a pressure testing machine and then maintained under pressure. The pressurization pressure of the testing machine was 160 MPa, and the holding time was 20 minutes. The repair material after dry pressing was subjected to 200 MPa cold isostatic pressing, and the repair material was obtained after maintaining the pressure.

[0127] Example 6

[0128] Weigh 24 wt% flocculent PVA solid and stir in a water bath at high temperature to prepare a 5% PVA solution. Weigh 10 g of the powder from Preparation Example 1, add it to the PVA solution, and grind it evenly in a mortar.

[0129] The powder after granulation is sieved through 50 mesh, 120 mesh and 300 mesh sieves respectively. The particles that can pass through 300 mesh sieve are fine particles, those between 120-300 mesh are medium particles, and those between 50-120 mesh are coarse particles.

[0130] According to the set particle size distribution, weigh 6g of coarse, medium and fine powders in total, with the coarse, medium and fine powders in a ratio of 5:4:1, and put them into the mold;

[0131] The sample was slowly pressurized by a pressure testing machine and then maintained under pressure. The pressurization pressure of the testing machine was 120 MPa, and the holding time was 20 minutes. The repair material after dry pressing was subjected to 200 MPa cold isostatic pressing, and the repair material was obtained after maintaining the pressure.

[0132] Example 7

[0133] Weigh 14 wt% flocculent PVA solid and stir in a water bath at high temperature to prepare a 5% PVA solution. Weigh 10 g of the powder from Preparation Example 1, add it to the PVA solution, and grind it evenly in a mortar.

[0134] The powder after granulation is sieved through 50 mesh, 120 mesh and 300 mesh sieves respectively. The particles that can pass through 300 mesh sieve are fine particles, those between 120-300 mesh are medium particles, and those between 50-120 mesh are coarse particles.

[0135] According to the set particle size distribution, weigh 6g of coarse, medium and fine powders in total, with the coarse, medium and fine powders in a ratio of 5:4:1, and put them into the mold;

[0136] The sample was slowly pressurized by a pressure testing machine and then maintained under pressure. The pressurization pressure of the testing machine was 80 MPa, and the holding time was 20 minutes. The repair material after dry pressing was subjected to 200 MPa cold isostatic pressing, and the repair material was obtained after maintaining the pressure.

[0137] Example 8

[0138] Weigh 14 wt% flocculent PVA solid and stir in a water bath at high temperature to prepare a 5% PVA solution. Weigh 10 g of the powder from Preparation Example 1, add it to the PVA solution, and grind it evenly in a mortar.

[0139] The powder after granulation is sieved through 50 mesh, 120 mesh and 300 mesh sieves respectively. The particles that can pass through 300 mesh sieve are fine particles, those between 120-300 mesh are medium particles, and those between 50-120 mesh are coarse particles.

[0140] According to the set particle size distribution, weigh 6g of coarse, medium and fine powders in total, with the coarse, medium and fine powders in a ratio of 6:3:1, and put them into the mold;

[0141] The sample was slowly pressurized by a pressure testing machine and then maintained under pressure. The pressurization pressure of the testing machine was 120 MPa, and the holding time was 20 minutes. The repair material after dry pressing was subjected to 200 MPa cold isostatic pressing, and the repair material was obtained after maintaining the pressure.

[0142] Example 9

[0143] Weigh 4 wt% flocculent PVA solid and stir in a water bath at high temperature to prepare a 5% PVA solution. Weigh 10 g of the powder from Preparation Example 1, add it to the PVA solution, and grind it evenly in a mortar.

[0144] The powder after granulation is sieved through 50 mesh, 120 mesh and 300 mesh sieves respectively. The particles that can pass through 300 mesh sieve are fine particles, those between 120-300 mesh are medium particles, and those between 50-120 mesh are coarse particles.

[0145] According to the set particle size distribution, weigh 6g of coarse, medium and fine powders in total, with the coarse, medium and fine powders in a ratio of 6:3:1, and put them into the mold;

[0146] The sample was slowly pressurized by a pressure testing machine and then maintained under pressure. The pressurization pressure of the testing machine was 80 MPa, and the holding time was 20 minutes. The repair material after dry pressing was subjected to 200 MPa cold isostatic pressing, and the repair material was obtained after maintaining the pressure.

[0147] Performance testing

[0148] The repair materials prepared in Examples 1 to 9 were placed in a constant temperature drying oven and dried at 100±50°C for 5 hours. After being taken out of the drying oven, they were cooled to 25°C and the mass of the repair materials was measured. The repair materials were placed in a beaker and placed in a pore density meter. The vacuum was evacuated to 2.66 KPa and the pressure was maintained for 10 minutes. The immersion liquid was slowly injected into the beaker until the liquid completely immersed the sample. The pressure was maintained for 5 minutes. The repair materials were carefully taken out with tweezers. The gauze was saturated with the immersion liquid and the excess liquid on the surface of the repair material was wiped off. The mass in the air was weighed. The sample was placed in a gold wire mesh with tweezers to ensure that the immersion liquid completely immersed the repair material and the gold wire mesh. The gold wire mesh could not touch the bottom and wall of the container. The mass of the repair material in water was weighed. The theoretical density of the repair material is the ratio of the mass of the repair material to the actual volume when it does not contain any pores. The test results are as follows.

[0149]

[0150] The test results show that the present invention forms a thin film between the powder particles by adsorbing PVA on the surface of the powder particles, which is used to reduce friction. The loose density of the powder after granulation is large, the volume compression rate during molding is small, and it is easy to be pressed into a repair material with a dense structure. The pores on the surface and inside of the repair material are reduced, and it is not easy to break.

[0151] Obviously, the embodiments described are only some of the embodiments of the present invention, rather than all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without making creative work should fall within the scope of protection of the present invention. Structures, devices, and operating methods not specifically described and explained in the present invention shall be implemented in accordance with conventional means in the field unless otherwise specified or limited.

Claims

1. The preparation process of zirconium oxide composite antibacterial repair material is characterized by: The following steps are involved: Step 1: Weigh ZrO(NO3)2.2H2O to make a solution, place it in a heating stirrer and heat and stir; Step 2: Add 6% mol Y(NO3)3.6H2O and KCl to the liquid in step 1, and continue heating and stirring until dissolved; Step 3: Add CH4N2O to step 2, heat and stir until dissolved; Step 4: When the nitrate mixed solution is concentrated into a viscous liquid, stop heating, pour the viscous liquid into a crucible, place it in a resistance furnace, ignite it at a constant temperature, and keep it warm for two minutes to obtain a powder; Step 5: Pour the powder into a beaker, add distilled water and stir to dissolve, use a sedimentation machine to filter and remove chloride ions, filter and wash five times, and finally add silver nitrate solution to the filtrate for testing. If no precipitate is produced, there is no chloride ion; Step 6: Wash with anhydrous ethanol to replace distilled water, and use an ultrasonic cleaner to clean for ten minutes; Step 7: Put the wet powder into a freeze dryer to dry it to obtain powder; Step 8: Weigh the flocculent PVA solid, stir it in a water bath at high temperature to prepare a PVA solution with a mass fraction of 5%, weigh 10g of powder, add it to the PVA solution, and grind it evenly with a mortar; Step 9: The granulated powder is sieved through 50 mesh, 120 mesh and 300 mesh sieves respectively. The particles that can pass through the 300 mesh sieve are fine particles, those between 120-300 mesh are medium particles, and those between 50-120 mesh are coarse particles. Step 10: According to the set particle size distribution, weigh 6g of coarse, medium and fine powders and put them into the mold; Step 11: Slowly pressurize the sample with a pressure testing machine, maintain the pressure, and perform 200Mpa cold isostatic pressing on the repair material after dry pressing, and obtain the repair material after maintaining the pressure.

2. The preparation process of the zirconium oxide composite antibacterial repair material according to claim 1, characterized in that: The concentration of the solution in step 1 is 0.085 mol / L to 0.34 mol / L.

3. The preparation process of the zirconium oxide composite antibacterial repair material according to claim 1, characterized in that: In the step 3, the ratio of urea to metal nitrate is 0.5-1.

5.

4. The preparation process of the zirconium oxide composite antibacterial repair material according to claim 1, characterized in that: In the step 4, the temperature of the constant temperature ignition is 400°C-600°C.

5. The preparation process of the zirconium oxide composite antibacterial repair material according to claim 3, characterized in that: In the step 3, when the ratio of urea to metal nitrate is 1.5, concentrated nitric acid needs to be added.

6. The preparation process of the zirconium oxide composite antibacterial repair material according to claim 1, characterized in that: The ratio of KCl to metal nitrate is 3-5.

7. The preparation process of the zirconium oxide composite antibacterial repair material according to claim 1, characterized in that: The mass percentage of the flocculent PVA solid is 4wt%-24wt%.

8. The preparation process of the zirconium oxide composite antibacterial repair material according to claim 1, characterized in that: In the step 10, the ratio of coarse, medium and fine powders is 6:3:1 or 5:4:1 or 0:7:

3.

9. The preparation process of the zirconium oxide composite antibacterial repair material according to claim 1, characterized in that: In the step 11, the pressurization pressure of the testing machine is 80Mpa-160Mpa, and the pressure holding time is 20min.